Kualitas Pelayanan Jemput Bola bagi Warga Disabilitas di Dinas Kependudukan dan Pencatatan Sipil Kota Cimahi - Choerunnisa, Raisa Rafifiti; Rosinta, Rosinta (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2023)
Cimahi City Government initiated â€œjemput bolaâ€ public service for citizen with disability. â€œJemput bolaâ€ public service is an act of recording electronic citizen identity card (e-KTP) for citizen with disabilty, elderly, and acute sickness by going directly to the their houses. This study aimed to determine the implementation of population administration services through â€œjemput bolaâ€ public service for citizen with disability at the Population and Civil Registration Office of the Cimahi City along with the obstacles that occured during the process. The research method used was qualitative research. Sources of data in this study were interview, direct observation, and document study. The results of this study indicated that in carrying out ball â€œjemput bolaâ€ public service for citizen with disability, there were some obstacles, i.e.: the absence of Standard Operating Procedures, internet network quality, character of citizen with disability, and access toward citizenâ€™s house location. To overcome the main obstacles, researchers created a Standard Operating Procedure document as guidance for â€œjemput bolaâ€ public service for citizen with disability. For internet network problem, officers could prepare a specific internet network system that was worked in the targeted area and also brought up a backup network. For obstacle related to mood disturbance of citizen with disability, officers needed special training to handle challenging situation so they could serve them in a more appropriate way. For obstacle related to access toward citizenâ€™s house location, officers could bring recording equipment to citizenâ€™s house. This research could benefit Cimahi City Office of Population and Civil Registration to improve the quality of â€œjemput bolaâ€ public service for citizen with disability and also as reference for similar research.